Identification of Group II Intron RmInt1 Binding Sites in a Bacterial Genome - Molina-Sánchez, María Dolores; García-Rodríguez, Fernando Manuel; Andrés-León, Eduardo; Toro, Nicolás (Frontiers in Molecular Biosciences, 2022)
RmInt1 is a group II intron encoding a reverse transcriptase protein (IEP) lacking the C-terminal endonuclease domain. RmInt1 is an efficient mobile retroelement that predominantly reverse splices into the transient single-stranded DNA at the template for lagging strand DNA synthesis during host replication, a process facilitated by the interaction of the RmInt1 IEP with DnaN at the replication fork. It has been suggested that group II intron ribonucleoprotein particles bind DNA nonspecifically, and then scan for their correct target site. In this study, we investigated RmInt1 binding sites throughout the Sinorhizobium meliloti genome, by chromatin-immunoprecipitation coupled with next-generation sequencing. We found that RmInt1 binding sites cluster around the bidirectional replication origin of each of the three replicons comprising the S. meliloti genome. Our results provide new evidence linking group II intron mobility to host DNA replication.